Concepção de atitudes em relação à marca de refrigerante de cola a partir do modelo de equivalência de estímulos - Souza, Thamyres Ferreira de (2022)
The stimulus equivalence paradigm allows for the experimental identification of symbolic functions and has been used to verify attitudes with regard to their evaluative nature. This research investigated the extent to which participants' pre-experimental history can interfere with their attitudes toward brands. Twenty college students were trained to respond to a brand, an abstract painting, and a negative face as being equivalent. A brand relationship form was used to investigate each individual's history toward the soft drink. Symmetry and transitivity relation tests were conducted after training. Most participants related the brand to the negative face. It was possible to verify that pre-experimental history has a relationship with the formation or not of equivalence classes.